The Difference in Blood Pressure Using the Open Extraction Method Before and After Local Anesthesia with Lidocaine + Adrenaline 1:80,000 at RSGM Nala Husada - Mecthildis Vianeys; Eddy Hermanto (Denta Journal Kedokteran Gigi, 2025)
Background: Local anesthesia is the first step before open method extraction. The local anesthesia contains 2% lidocaine and adrenaline in a 1:80,000 ratio to extend its duration and reduce the risk of toxicity. However, the use of vasoconstrictors may lead to a spike in blood pressure. Objective: To determine the difference in blood pressure before and after the administration of lidocaine + adrenaline in a 1:80,000 ratio for open method extraction at RSGM Nala Husada Surabaya. Materials and Methods: Blood pressure was measured before and after the administration of local anesthesia containing lidocaine + adrenaline in a 1:80,000 ratio for open method extraction, following the inclusion criteria with a sample size of 21. Blood pressure was measured using an "Omron HEM-FL31" digital sphygmomanometer. Data analysis was performed using a paired t-test. Results: The paired t-test results showed a significant difference in systolic blood pressure (p<0.05), but no significant difference in diastolic blood pressure (p>0.05) before and after the administration of local anesthesia for open method extraction patients. The systolic blood pressure showed the highest value after the administration of local anesthesia (122.95 ± 14.59). Conclusion: Blood pressure showed a significant difference before and after the administration of local anesthesia containing lidocaine + adrenaline in a 1:80,000 ratio for open method extraction at RSGM Nala Husada Surabaya.